Paradigma Baru dalam Audit Internal - Irawan, Ronny (Jurnal Widya Manajemen & Akuntansi, 2003)
The changes of business environment caused transformation of the role of internal auditing in any organization. In traditional concept, the role of internal auditor is a faultfinder, perform reperforming, and then move away to control as a focus, finally to add value and improve an organization' operations. They represent as a Part of organization provides a service of value to the organization, as a consultant and helps an organization accomplish its objectives. This new paradigms gives opportunities and challenges for internal auditor to improve their knowledge's and skills broadly.